PENGEMBANGAN INSTRUMEN PENILAIAN KOGNITIF DALAM PEMBELAJARAN TEMATIK KELAS 5 SD - Utami, Diah Ayu Putri; Wardani, Naniek Sulistya (LPPM STKIP PGRI Bandar Lampung, 2020)
The purpose of this research is to know about 1) how to improve knowledge scoring instrument in theme of grade 5 elementary school; 2) quality knowledge scoring instrument in thematic of grade 5 from analysis the test. The type of this research is Research and Development (R&D) from Borg & Gall that modified by Sukmadinata. This research have 3 procedures, 1) preliminary studies, 2) improve the product, 3) product trial. The subject of this research is Students of grade 5 Dorolegi 1 elementary school, 1 Ketangirejo elementary school, and 1 Sindurejo elementary School in Grobogan. The type of data used primer from test technique that was multiple choice instrument. Analysis technique used classic items. The results of the study show that 1) how to improve knowledge scoring instrument used theme, KI,KD, Indicators of Competence Achievement, measuring instrument, grid, item, trial 1, trial 1, revision 1, trial 2, item 2 analysis, revision 2, trial 3, item 3 analysis, determine final product. 2) Instrument of the multiple choices item consisted of 42 items. From a classic analysis, the items have validity r>0,20, medium reliable reliability 0,25<P<0,75, distinguishing power received P<0,20, bleach power 59,5% works very well and 40,5% bleach power works well. Over that, knowledge scoring instrument in theme 6 heat and displacement of grade 5 suitable for use as a good instrument